Impact of import substitution policy on economic growth - Askar Nailevich Mustafin; Svetlana Nikolaevna Kotenkova; Ivana Kravčáková Vozárová; Rastislav Kotulič (Economies, 2022)
This paper highlights the issues of import substitution in the context of attaining total macro-economic balance, market adaptation, and achieving new levels of regional economic development as a constituent part of the national economy of the Russian Federation. An effective strategy and goal management are the important forward-looking orientation points of the existence and development of the country. In this study, we tested the hypothesis that economic growth in the region can be estimated via the GRP per capita. To define the sectors and regions with a successful implementation of a substitution policy, our own special algorithm for sorting and classifying regions was used. This algorithm made it possible to estimate the effectiveness of the economic policy, if any. To confirm and estimate the hypothesis, tests based on panel data models were carried out. The results revealed that the economic policy of import substitution was 10% more efficient in the regions where it was implemented than those without an implemented policy.
Keywords: 330; economic growth; import substitution; macro-economic balance; market adaptation; regions